Establishing child-friendly environments a study on the elementary schools in Tagum City, Philippines - Boiser, Denise Loiuse M. (2021)
A school, which is an important personal and social space in children?s lives is an environment essential to a child?s development. A child- friendly school environment must ensure a child a space that is physically safe, emotionally secure, and psychologically enabling. It is essential that schools provide an environment that will help them reach their goal development at this age and studies show that children learn faster and better when they are able to assert their independence while doing tasks. The study examined the child-friendliness of elementary school environments in Tagum City, Philippines in the light of the Bullerby Model. The Bullerby Model suggests that a child-friendly environment is an environment where children are able to actualize environmental affordances independently. This research is both quantitative and qualitative research and underwent statistical and content analysis. The children were asked which places in school they considered their favorites and were asked to identify what environmental affordances they were able to actualize in these spaces. The results of the study revealed which spaces in the school environment were hotspot locations for actualized environmental affordances. These spaces were further examined by identifying the supportive environmental qualities of the space. To tackle the sociocultural factors, the children?s field of actions were also surveyed. The results of the study revealed what spaces are fundamental in a child-friendly elementary school. The study showed that children are able to actualize more affordances in spaces where children and social interactions are visible. Natural environment fostered more environmental affordances than the indoor spaces. These results, together with the results of the frequency analysis of the actualized environmental affordances and the content analysis of the supportive environmental qualities of spaces were fundamental in the formulation of design guidelines for a child-friendly school environment.